Effectiveness of life skills training on the cognitive, behavioral, emotional and motivational skills of students with mathematical disorder - Seyede Somayeh Jalilabkenar; Mohammad Ashoori; Masoumeh Poormohammadrezay Tajrishi (Vesnu Publications, 2013)
Introduction: Many research studies have been made on the effectiveness of life skills training program on cognitive, behavioral, emotional, and motivational skills in normal students. While afew investigations have been conducted about the effect of this program on mentioned variables simultaneously, in students with mathematical disorders. The aim of this study was to determine the effect of life skills training programs on cognitive, behavioral, emotional, and motivational skills in students with mathematical disorder. Materials and Methods: The present research was a quasi-experimental study by pre-post test design with control group. Participants were forty boy students aged from 13-15 years old with mathematical disorder. This sample size was randomly recruited from some learning disorder schools in Tehran province. Participants were equally divided into two groups of experimental and control. Subjects in experimental group received life skill training program in 9 sessions while, control group did not receive any intervention. Wechsler intelligence test, key Math diagnostic mathematic test, life skills training program of world health organization and social self-competence questionnaire of Felner, Lease and Philips were used to collect the data. The obtained data were statistically analyzed by MANOVA using SPSS, version 16. Results: The results of MANOVA showed that the experimental and control groups had a significant difference, At least in one of the sub-scales of the cognitive, behavioral, emotional,and motivational skills (F = 13.27, P < 0.001). The final results of MANOVA showed that the life skills training program had a significant and positive effect on cognitive skill (F = 8.78, P < 0.010), behavioral skill (F = 22.37, P < 0.050), emotional skill (F = 5.51, P < 0.010), and motivational skill (F = 17.42, P < 0/010). Conclusion: Life skills training program could have a significant effect on cognitive, behavioral, emotional, and motivational skills in students with mathematical disorders. Since enhancement of these skills can lead to social competence of students, planning for life skills training is of particular importance for students with mathematical disorders. Keywords: Life skills, Cognitive, Behavioral, Emotional and motivational skills, Mathematical disorders